An analysis of the quiet time day‐to‐day variability in the formation of postsunset equatorial plasma bubbles in the Southeast Asian region. Issue 4 (30th April 2014) - Carter, B. A.; Yizengaw, E.; Retterer, J. M.; Francis, M.; Terkildsen, M.; Marshall, R.; Norman, R.; Zhang, K.
Abstract Presented is an analysis of the occurrence of postsunset Equatorial Plasma Bubbles (EPBs) detected using a Global Positioning System (GPS) receiver at Vanimo. The three year data set shows that the EPB occurrence maximizes (minimizes) during the equinoxes (solstices), in good agreement with previous findings. The Vanimo ionosonde station is used with the GPS receiver in an analysis of the day‐to‐day EPB occurrence variability during the 2000 equinox period. A superposed epoch analysis (SEA) reveals that the altitude, and the change in altitude, of the F layer height is ∼1 standard deviation (1σ) larger on the days for which EPBs were detected, compared to non‐EPB days. These results are then compared to results from the Thermosphere Ionosphere Electrodynamics General Circulation Model (TIEGCM), which show strong similarities with the observations. The TIEGCM is used to calculate the flux‐tube integrated Rayleigh‐Taylor (R‐T) instability linear growth rate. A SEA reveals that the modeled R‐T growth rate is 1σ higher on average for EPB days compared to non‐EPB days, and that the upward plasma drift is the most dominant contributor. It is further demonstrated that the TIEGCM's success in describing the observed daily EPB variability during the scintillation season resides in the variations caused by geomagnetic activity (as parameterized by Kp) rather than solar EUV flux (as parameterized by F10.7). Geomagnetic activity varies the modeled high‐latitude plasma convection and the associated Joule heating that affects the low‐latitude F region dynamo, and consequently the equatorial upward plasma drift.